V.N. Institute of Forest Arboretum, Krasnoyarsk as the Object of Ecological Education - Bazhina Ekaterina Alexandrovna; Bazhina Elena Vasilievna; Koretc Mihail Anatolievitch (Hortus Botanicus)
The essay presents the possibilities of using the Arboretum of the Forest Institute in the educational process of students of higher educational institutions. An important component of the activity of Botanical Gardens - science and education, obtaining and promoting modern scientific knowledge. Educational and demonstration work is an essential component of the activities of Botanical Gardens and Arboretums, regardless of university or academic affiliation, as well as regional, national and other characteristics. Visiting such facilities and taking students directly into the conditions of artificially created biocenoses contributes to the formation of an ecological imperative, an understanding of the importance of all life on Earth, an understanding of the diversity of plants and their determining role in ensuring sustainable livelihoods. Thousands of schoolchildren and students all over the world are involved in educational seminars, trainings and various courses organised by the Botanical Gardens. The collection of plants presented in the Arboretum of the Forest Institute allows conducting lectures-excursions (storytelling against the background of live objects), during which students develop a certain approach to explaining the phenomena of nature, understanding the biological and ecological characteristics of various species of conifers, in particular, their ability to adapt to climatic fluctuations. The Arboretum is a special type of communicative space, in which the properties and relations of external objects surrounding the student stimulate mental processes that awaken interest in learning, which contributes to better perception and memorisation of information. It is promising to use the Arboretum of the Forest Institute in the educational activities of students of a wide range of specialities, both biological and designers of various directions (in particular, in the course of Architect Environmental Design).